Platelet apoptosis and agonist-mediated activation in myelodysplastic syndromes - Martín, Mónica; de Paz, Raquel; Jiménez-Yuste, Víctor; Bello, Ihosvany Fernández; Salgado, Elena García Arias; Álvarez, María Teresa; Butta, Nora V. (Thrombosis and Haemostasis, 2013)
Patients with myelodysplastic syndromes (MDS) have a defect in the differentiation of bone marrow multipotent progenitor cells. Thrombocytopenia in MDS patients may be due to premature megakaryocyte death, but platelet apoptotic mechanisms may also occur. This study aimed to study function and apoptotic state of platelets from MDS patients with different platelet count. Reticulated platelets, platelet activation, activated caspases and annexin-V binding were evaluated by flow cytometry. Pro-apoptotic Bax and Bak proteins were determined by western blots and plasma thrombopoietin by ELISA. Microparticle-associated procoagulant activity and thrombin generation capacity of plasma were determined by an activity kit and calibrated automated thrombography, respectively. High plasma thrombopoietin levels and low immature circulating platelet count showed a pattern of hypoplastic thrombocytopenia in MDS patients. Platelets from MDS patients showed reduced activation capacity and more apoptosis signs than controls. Patients with the lowest platelet count showed less platelet activation and the highest extent of platelet apoptosis. On this basis, patients with thrombocytopenia should suffer more haemorrhagic episodes than is actually observed. Consequently, we tested whether there were some compensatory mechanisms to counteract their expected bleeding tendency. Microparticle-associated procoagulant activity was enhanced in MDS patients with thrombocytopenia, whereas their plasma thrombin generation capacity was similar to control group. This research shows a hypoplastic thrombocytopenia that platelets from MDS patients possess an impaired ability to be stimulated and more apoptosis markers than those from healthy controls, indicating that MDS is a stem cell disorder, and then, both number and function of progeny cells, might be affected.
Keywords: Platelet pathology; myelodysplastic syndromes; GP IIb/IIIa activation; platelet apoptosis